Large‐Scale Cross‐Sectional Serological Survey of Schmallenberg Virus in Belgian Cattle at the End of the First Vector Season. Issue 1 (3rd December 2012) - Méroc, E.; Poskin, A.; Van, H.; Quinet, C.; Van, E.; Delooz, L.; Behaeghel, I.; Riocreux, F.; Hooyberghs, J.; De, N.; Caij, A. B.; van den, T.; et al.
Summary A cross‐sectional survey was conducted in the Belgian cattle population after the first period of infection of the emerging Schmallenberg virus. A total number of 11 635 cattle from 422 herds sampled between 2 January and 7 March 2012 were tested for the presence of Schmallenberg‐specific antibodies using an ELISA kit. Between‐herd seroprevalence in cattle was estimated at 99.76% (95% CI: 98.34–99.97) and within‐herd seroprevalence at 86.3% (95% CI: 84.75–87.71). An Intraclass Correlation Coefficient of 0.3 (P < 0.001) was found, indicating that the correlation between two animals within a herd with respect to their serological status was high. Those results corroborate the conclusion that the Schmallenberg virus was widespread in Belgium during winter 2011. Seroprevalence was shown to be statistically associated to the animal's age (P < 0.0001): with 64.9% (95% CI: 61.34–68.3) estimated for the 6–12 months of age, 86.79% (95% CI: 84.43–88.85) for the 12–24 months of age and 94.4% (95% CI: 93.14–95.44) for the animals older than 24 months. Based on the results of the described serological survey, we can conclude that after the first Schmallenberg virus episode, almost every Belgian cattle has already been in contact with the virus. In consequence, the vast majority of the host animals should have developed post infection protective immunity against the virus.